Claiming for a fair share in the matrimonial partnership upon death: the right of the surviving spouse from the Malaysian legal perspective - Arshad, Azhani; Halim, Akmal Hidayah (2014)

(untitled)
One of the claims that may be made against the deceased’s estate is the claim by the surviving spouse for a fair share in the matrimonial assets acquired by parties during their marriage by their joint efforts. Whilst there is a clear provision on the right of the spouse to claim for a fair share in the matrimonial partnership upon divorce, the written law is silent on such a claim to be made upon death. As for the Muslims, a claim to matrimonial assets upon death is allowed based on the practice of the Syariah Courts which has recognised for such a claim to be made not only by the surviving spouse but also by the former spouse and estate beneficiaries. With regards to the non-Muslims, it is an established law that such a claim is only allowed to be made upon divorce, and not death. Hence, one question that has always nagged the surviving spouse is that how would he or she claims for a fair share in the matrimonial partnership upon death. Thus, this paper seeks to examine the position of such a claim from the Malaysian legal perspective and to analyse the present law and procedure for the purpose of such claim. The paper also aims to identify the possible method to claim for a fair share in the matrimonial assets for the non-Muslims under the law of contract and also under the law of trust. This paper employed the doctrinal analysis by examining the existing primary and secondary materials including statutory provisions as provided by the Islamic family law statutes and the Law Reform (Marriage and Divorce) Act 1976, case law and other legal and non-legal literatures relating to such claim.